Model Supply Chain Management pada Produk Industri Agraris dan Turunan - Muchammad Fariq Maulana; Nur Isnaini; Dea Nur Zuraidah; Yusuf Amrozi (Universitas Djuanda, 2020)
Implementation of Supply Chain Management is needed to meet consumer demand for agricultural products both for raw materials, as well as fresh and halal products for direct consumption so that they can benefit both farmers and consumers. The purpose of this study was to determine the supply chain mechanism and supply chain flow patterns of agroindustry products and analyze the effect of supply chain management components on improving agro-industry performance. The method attached to the source of the journal relating to the method to be used. The source deals with a deeper review of the FIFO (First In First Out) method in implementing SCM (Supply Chain Management) in agriculture. With this method work will be quickly completed, run effectively, generate profits with high profits. Supply chain is defined as a sequence of decision making processes regarding raw materials, information, and capital undertaken by a company to meet consumer demand. Supply Chain Management activities are implemented starting from the planning of raw materials and then proceed to the production process that is handled by the agrarian industry then the products are stored in warehouses using the FIFO (First In First Out) method then distributed to retailers to be marketed to consumers.Keywords: supply chain management, agro-industry, fifo